Peran Pemerintah Daerah terhadap Mutu Layanan Pemeriksaan Kesehatan Gratis di Puskemas Cimanggis - Joko Puratmo, AMG; Yunus, M.; Ghaffari, Muhammad; Januar Undur, Efar; Sekar Siwi, Dwi (Coopetition : Jurnal Ilmiah Manajemen, 2026)
The implementation of free health check programs reflects the local government’s effort to expand access to public healthcare services. However, its effectiveness often faces challenges in maintaining service quality at the primary healthcare level. This study aims to analyze the role of the Depok City Government in planning, implementing, and supervising the free health check program at Cimanggis Public Health Center (Puskesmas Cimanggis), as well as to examine its influence on perceived service quality. This research employs a qualitative descriptive approach through in-depth interviews, observations, and document studies, with data validity ensured by source and method triangulation. Findings reveal that the local government plays four essential roles: regulative, facilitative, capacitative, and supervisory. These roles contribute positively to improving the five SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—with the greatest enhancement observed in responsiveness and empathy. Key obstacles include limited medical personnel, uneven logistics distribution, and manual evaluation systems. The study concludes that the program’s success depends on adaptive policy implementation, human resource capacity strengthening, and the digitalization of service systems based on a humanistic service approach. Keywords: Local Government, Service Quality, Free Health Check Program, SERVQUAL.